Case report of pyloric obstruction caused by giant gallbladder compression with literature review - Xu, Wenhui; Liu, Panpan; Ni, Qinyu; Cao, Xuedong; Liu, Kun; Xue, Shigui; Gao, Yueqiu; Zhu, Xiaojun (Frontiers in Surgery, 2026)
Giant gallbladder is a rare clinical condition characterized by abnormal gallbladder enlargement, typically defined as a longitudinal diameter exceeding 14 cm or a volume surpassing 1.5 L. The most common pathological etiologies are cholelithiasis and chronic cholecystitis, followed by neoplastic factors, while congenital developmental anomalies and other causes are relatively uncommon. Herein, we report a case of giant gallbladder-induced pyloric obstruction in a patient who presented with nausea and vomiting for two weeks—symptoms that recurred after initial resolution of diabetic ketoacidosis. Abdominal computed tomography (CT) revealed a giant gallbladder with cholelithiasis, and gastroscopy demonstrated an extrinsic compressive bulge in the gastric antrum plus narrowing at the second and third part of duodenum (D2 & D3).The patient was diagnosed with cholelithiasis and chronic cholecystitis leading to giant gallbladder, which caused pyloric obstruction via compression. Management involved initial ultrasound-guided percutaneous gallbladder drainage, followed by laparoscopic cholecystectomy (LC) one week later, and the postoperative course was uneventful. This case highlights that giant gallbladder may present with atypical gastrointestinal symptoms (e.g., isolated nausea and vomiting) and is prone to misdiagnosis, especially in middle-aged and elderly females with comorbidities. Confirmation of the compressive mechanism requires integration of imaging and endoscopic findings; for patients with giant gallbladder complicated by severe adhesions or underlying comorbidities, a two-stage surgical approach (initial decompressive drainage followed by laparoscopic excision) is a safe and effective option.